Pengembangan Potensi Nelayan Melalui Pelatihan Manajemen Usaha Pengolahan Ikan Asap Di Gks Hanggaroru, Desa Kaliuda - Yatris Rambu Tega; Elfis U. K. Retang; Krisman U. Henggu; Suryaningsih Ndahawali; Firat Meiyasa (Pusat Riset dan Inovasi Nasional, 2024)
Fisheries, especially capture fisheries, have quite large potential in the coastal area of ​​East Sumba. One of the potential catch fisheries in East Sumba is Kaliuda Village. The GKS Hanggaroru congregation is a community in Kaliuda village whose entire community depends on fishery products, both capture and aquaculture. Fisheries problems that often occur in Kaliuda village are the large number of catches that are damaged due to the way they are handled after being caught, due to the unavailability of ice, and the length of the marketing process. This results in losses at the community level so it is necessary to find a solution regarding partnerships and marketing the catch. This mentoring activity was carried out for 1 month through socialization and mentoring. Implementation of this activity includes socialization, distribution of leaflets on procedures for making smoked fish, training in making smoked fish using a cabinet with a separate smoke source using a drum, as well as designing packaging and packaging using a vacuum sealer. Partners are happy with the training activities carried out by the PKM team.